Sexual differentiation and of sex determination - Özbey, Ülkü; Yüce, Hüseyin (My University, 2007)
Sex determination and differentiation is a sequential process that involves genetic, gonadal, phenotypic and psychological sex. Sex differentiation begins in the embryo under genetic and hormonal control. Sex determination is primarily a testis determination. The primary event is differentiation of the gonad; all subsequent sexual differentiation is hormonally controlled. In humans, gender is assigned at birth. Then, individuals grow under social environment provided according to the gender assigned and acquire gender role during childhood and gender identity during puberty. Therefore, knowledge of pathogenesis and clinical morphology of congenital disturbances of sexual differentiation helps to establish earlier hermaphroditism variant, appropriate surgery for complete socio-psychological adaptation of this group of patients. The mechanisms for sex differentiation and the genes on the sex chromosomes are varied among different species. For human beings, SRY is the only testis-determining factor on the Y chromosome and it triggers the cascade for male sex-determination. This gene initiates the cascade of reactions which leads to the differentiation of bipotential, indifferent gonads to testes or ovaries, depending on the presence or absence of active SRYs. Many other autosomal genes, present in both males and females are expressed during testis formation in a gene activation pathway. Elucidation of the genetic cascade will help us to understand the molecular mechanisms underlying gonadal differentiation and gonad sex differentiation.
Cinsiyet farklilaşmasi ve belirlenmesi
Keywords: congenital malformation; embryo development; gender identity; gene activation; genetic regulation; gonad development; heredity; hermaphroditism; hormonal regulation; human; medical education; morphological trait; morphology; ovary cell; psychological aspect; puberty; review; sex chromosome; sex determination; sex differentiation; social environment; social psychology; testis development